1980
DOI: 10.1016/s0022-5347(17)55275-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface A, B or O(H) Blood Group Antigens as an Indicator of Malignant Potential in Stage A Bladder Carcinoma

Abstract: The major blood group antigens A, B or O(H) are present on normal bladder epithelium. The presence or absence of these antigens on the cell surface of bladder tumors has been determined in a retrospective longitudinal study using biopsy material from 322 patients who fit the following criteria: 1) the patient presented initially with a superficial bladder tumor, 2) the patient had followup examination for at least 5 years or until evidence of tumor invasion of bladder muscle and 3) the paraffin-embedded tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(22 citation statements)
references
References 7 publications
2
19
0
1
Order By: Relevance
“…These findings were confirmed by us and other groups [14,19,20,25,30], If we discuss the findings of this prospec tive study we have to keep in mind the small number of patients. However, we assume that a high percentage of patients with a tumor deleted of ABH antigens will also re veal an impaired immune status assessed in this study by the DNCB skin test and MC.…”
Section: Discussionsupporting
confidence: 84%
“…These findings were confirmed by us and other groups [14,19,20,25,30], If we discuss the findings of this prospec tive study we have to keep in mind the small number of patients. However, we assume that a high percentage of patients with a tumor deleted of ABH antigens will also re veal an impaired immune status assessed in this study by the DNCB skin test and MC.…”
Section: Discussionsupporting
confidence: 84%
“…A reduction in blood-group A antigen (GalNAca1-3[Fuca1-2]Galb1-3GlcNAc-R) expression was reported in transitional cell carcinoma (TCC) of the bladder and showed significant correlation with an invasive phenotype. [8][9][10][11] Orntoft and Wolf 12 examined the correlation between blood-group antigen expression and the activity of glycosyltransferases in TCC of the bladder and reported that the activity of A glycosyl transferase was severely reduced in tumors showing loss of A antigen expression. This phenomenon drew our attention, due to the fact that the determinant of the ABO blood-group antigen is synthesized by the action of the ABO gene encoding ABO glycosyltransferase assigned to chromosome 9q34.1, where loss of heterozygosity (LOH) was frequently reported in bladder cancer.…”
mentioning
confidence: 99%
“…It was also found that as individuals age they tend to develop high grade tumors. The possibility is that the presence or absence of blood group isoantigens is merely a reflection of the prevailing tumor grade [ 19], On the other hand, as far as immunity was concerned, the activation of the surface antigen decreases, while age increases; therefore, the aged are at greater risk [12]. In a study on 146 patients with superfi cial bladder tumors, with a follow-up examination for more than 5 years, Newman et al [ 19] found that 87% of the patients without recurrence were positive in surface antigens, while only 13% were negative.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility is that the presence or absence of blood group isoantigens is merely a reflection of the prevailing tumor grade [ 19], On the other hand, as far as immunity was concerned, the activation of the surface antigen decreases, while age increases; therefore, the aged are at greater risk [12]. In a study on 146 patients with superfi cial bladder tumors, with a follow-up examination for more than 5 years, Newman et al [ 19] found that 87% of the patients without recurrence were positive in surface antigens, while only 13% were negative. Besides, Berg man and Javadpour [20] also showed that among 5 patients without the recurrent tumors, 3 (60%) retained A, B or H antigen, whereas all of the 9 patients with recurrent tumors lost the surface antigens.…”
Section: Discussionmentioning
confidence: 99%